O crescimento econômico do município de Cafelândia, Paraná: uma análise de 1987 a 2022 - Frehner, Alícia Leal (2024)
This study analyzed the economic growth of the county of Cafelândia, Paraná based on the behavior of its productive sector between the years 1987 and 2022. In 1975, the coffee production was interrupted by the combination of economic, political and climatic factors. In the midst of the scenario presented, in 1982, the local cooperative began agro-industrial activities by installing a poultry integration system. From then on, there was sustained growth in this segment and some aspects of the regional development of theorists Douglass Cecil North, François Perroux and Albert Otto Hirschman could be identified in its process. The results of the study found through the statistical and technical method of regional analysis of the Locational Quotient (QL) indicator showed that Cafelândia developed the maintained specializations related to the performance of the agro-industrial segment, that is, in the activities of food, beverage and ethyl alcohol industry, services in accommodation, food, repair, maintenance, writing, etc. and in transport and communications. Secondarily, specializations linked to the urban growth also presented significant results due to the territorial agglomeration entailed by the same agro-industrial segment. In this sense, the work concluded that the counties' economic growth presents a consolidated productive distribution but concentrated and with few diversification.